Discourse analysis after the computational turn: a mixed bag. Issue 1 (2nd January 2023) - Matheson, Donald
ABSTRACT: This paper seeks to clarify a methodological agenda for combining discourse analysis with corpus analysis. It details four concerns. Firstly, it argues that corpus-assisted discourse analysis can quite drastically narrow the view on discourse, if used on its own and without accompanying theoretical tools for exploring social practice. Secondly, corpora are of more value in helping researchers identify the symbolic resources that people have available to them than at understanding how they use those resources. Thirdly, they must be approached through a renewed appreciation of communication as a human accomplishment and corpora must, therefore, be reconnected to the producers of that discourse. And fourthly, corpora are of greater value when extended beyond lexical analysis. Underpinning these points is a commitment to discourse analysis as a tool to understand in close detail how people use language to do things in their lives.